2000
DOI: 10.1111/j.1553-2712.2000.tb00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injuries Evaluated in U.S. Emergency Departments, 1992‐1994

Abstract: Abstract. Objective: To describe the incidence and patient characteristics of traumatic brain injuries (TBIs) treated in U.S. emergency departments (EDs). Methods: A secondary analysis was performed on data from the National Hospital Ambulatory Medical Care Survey administered from 1992 to 1994. An ED visit was determined to represent a case of TBI if the case record contained ICD-9-CM codes of 800.0-801.9, 803.0-804.9, or 850.0-854.1. Results: The average annual estimate of new TBI treated in U.S. EDs was 1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
170
2
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(185 citation statements)
references
References 8 publications
3
170
2
10
Order By: Relevance
“…1,9,10,36 In comparison to the findings of the present study, higher estimates of nonfatal injury rates (approximately 12 per 100) and lower proportions in the home environment (approximately 25%) in young children have been reported using the National Health Interview Survey (NHIS) and the NHAMCS. 1,10,37,38 Scheidt et al also found slightly higher rates of medicallyattended home injury (16 events per 100 children) using the Child Health Supplement to the 1988 NHIS over a 12-month recall period. 9 The inclusion of office and non-ED visits in the NHIS contributed to the higher rate estimate for nonfatal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,10,36 In comparison to the findings of the present study, higher estimates of nonfatal injury rates (approximately 12 per 100) and lower proportions in the home environment (approximately 25%) in young children have been reported using the National Health Interview Survey (NHIS) and the NHAMCS. 1,10,37,38 Scheidt et al also found slightly higher rates of medicallyattended home injury (16 events per 100 children) using the Child Health Supplement to the 1988 NHIS over a 12-month recall period. 9 The inclusion of office and non-ED visits in the NHIS contributed to the higher rate estimate for nonfatal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been estimated that at least 25% of persons experiencing a mild TBI (mTBI; often referred to as concussion) do not seek hospital care. 2 mTBI may result from a variety of insults, including a direct impact to the head, a rapid change in head motion (acceleration or deceleration), or an explosive blast, and can result in structural, physiological, and/or functional changes in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Vários estudos têm examinado a associação entre a TC de crânio, a gravidade da lesão e o prognóstico (Gennarelli et al, 1982;Greene et al, 1995;Kido et al, 1992;Wardlaw et al, 2002 (Gennarelli et al, 1982;Eisenberg et al, 1990;Selladurai et al, 1992;Kakarieka et al, 1994;Greene et al, 1995;Greene et al, 1996;Chesnut et al, 2000;Ono et al, 2001;Servadei et al, 2002 (Annegers et al, 1980); em San Diego as maiores taxas foram constatadas na faixa etária de 16 a 25 anos (Kraus et al, 1984) e no Bronx, o pico de incidência foi verificado na faixa etária de 16 a 30 anos (Cooper et al, 1983 ( Durkin et al, 1998). No entanto, em um estudo científico realizado em Minnesota entre 1965 a 1972, incluindo todos os casos de TCE, de todas as faixas etárias, foi detectado que 15% dos casos encontrava-se na faixa etária de 0 a 1 ano, 17% na de 2 a 10 anos e 26% na faixa etária de 11 a 20 anos (Annegers et al, 1980 (Jager et al, 2000) e de 1,5:1 no período de 1995 a 1996 (Guerrero et al, 2000).…”
Section: Introductionunclassified